ПОНЯТТЯ ТА ОСОБЛИВОСТІ КОРПУСУ ОПЕРАТИВНО-РАПТОВОЇ ДІЇ ЯК СПЕЦІАЛЬНОГО ПІДРОЗДІЛУ НАЦІОНАЛЬНОЇ ПОЛІЦІЇ УКРАЇНИ - Худоба, Іван Станіславович (SUPREMANCE OF LAW, 2018)
The article substantiates the urgency of creating a new unified special police unit in Ukraine. The preconditions and the state of creation of the Corps of the Operative-Flash Action (KORD) are characterized. The essence of the activity and tasks assigned to this unit, the basic requirements and criteria for selecting applicants for service in it, are analyzed. As a result, the concept of KORD, and certain features of the KORD as a special unit of the National Police of Ukraine, were clarified.
Keywords: Corps of Corps of the Operative-Flash Action; KORD; police; National Police of Ukraine; special unit; special police.